MENOPAUSAL HORMONE THERAPHY – APPLICATION, RISKS AND BENEFITS IN CLINICAL PRACTICE - Aleksandra Wądołowska; Blanka Serafin-Juszczak; Maria Wydra; Zuzanna Mogilany; Jan Wojdal; Karolina Kusek; Barbara Przybył; Katarzyna Ciepłucha; Michał Wilk; Daniel Narożniak (International Journal of Innovative Technologies in Social Science, 2025)
Aim of the study: The aim of this review is to explore current evidence regarding physiological rationale, indications, contraindications and systemic use of MHT in clinical practice. Materials and methods: Literature reviewed was conducted in medical databases such as PubMed, UpToDate and relevant subject literature published within last 30 years. Results: Evidence indicates that early initiation (< 10 years after the onset of menopause) of combined estrogen-progestogen therapy significantly diminishes coronary events and prevents rapid bone loss, whereas later commencement increases ischaemic stroke and venous thrombo-embolism risk. Unopposed systemic oestrogen elevates endometrial-carcinoma incidence, and long-term systemic regimens may moderately increase breast-cancer risk. On the contrary, topical vaginal oestrogens reverse urogenital atrophy and lower recurrent urinary-tract infection rates with minimal systemic exposure. Conclusion: MHT consistently alleviates vasomotor symptoms and improves quality of life, but does not constitute first-line therapy for established osteoporosis or primary cardiovascular prevention The therapeutic value of MHT is contingent upon timing, formulation, route and patient-specific comorbidities. When used for the shortest necessary duration and accompanied by careful surveillance, MHT offers substantial symptomatic benefit with acceptable safety in appropriately selected women.